2013
DOI: 10.5966/sctm.2013-0017
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Knockdown of a Disease-Causing Gene in Patient-Specific Induced Pluripotent Stem Cells Using Lentiviral Vector-Based Gene Therapy

Abstract: Patient-specific induced pluripotent stem cells (iPSCs) hold great promise for studies on disease-related developmental processes and may serve as an autologous cell source for future treatment of many hereditary diseases. New genetic engineering tools such as zinc finger nucleases and transcription activator-like effector nuclease allow targeted correction of monogenetic disorders but are very cumbersome to establish. Aiming at studies on the knockdown of a disease-causing gene, lentiviral vector-mediated exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 55 publications
0
36
0
1
Order By: Relevance
“…After successful evaluation of AAT sgRNAs we attempted correction of the human Z-AAT gene in a previously published patient-specific iPSC line (hPi) generated from an individual with severe ZZ-AAT deficiency20. This cell line is homozygous for the E342K missense point mutation and has been used for functional hepatic disease modeling studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After successful evaluation of AAT sgRNAs we attempted correction of the human Z-AAT gene in a previously published patient-specific iPSC line (hPi) generated from an individual with severe ZZ-AAT deficiency20. This cell line is homozygous for the E342K missense point mutation and has been used for functional hepatic disease modeling studies.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we had compared the EF-1α short promoter (EFS), the full length EF-1α promoter and the CAG promoter for their resistance to transgene silencing in mouse iPSC20. We found that CAG was the most stable of these promoters and expression persisted even throughout differentiation in vitro and in vivo , and that expression was also stable in human iPSC even at low lentiviral vector copy numbers (VCN).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations